2019
DOI: 10.1186/s40880-019-0406-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of lymphotropic invasive micropapillary breast carcinoma analyzed by using data from the National Cancer Database

Abstract: BackgroundInvasive micropapillary carcinoma (IMPC) is an uncommon subtype of breast cancer. Previous studies of this subtype demonstrated a higher propensity for lymph node metastases as compared with invasive ductal carcinoma (IDC). The purpose of the present study was to determine the clinical characteristics, outcomes, and propensity for lymph node metastasis of patients with IMPC of the breast recorded in the National Cancer Database (NCDB).MethodsRecords of patients with IMPC diagnosed between 2004 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 65 publications
2
38
0
4
Order By: Relevance
“…Complete surgical resection of the lesion is an important therapy in IMPC (5). However, IMPC is typically irregular in shape on MRI and the border is unclear (8,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete surgical resection of the lesion is an important therapy in IMPC (5). However, IMPC is typically irregular in shape on MRI and the border is unclear (8,10).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic invasion and lymph node metastasis are common in IMPC, with an incidence of nodal metastases of 24.9%, leading to frequent recurrence and poor prognosis in patients, with a 5-year overall survival rate of 87.5% (5). Even when the proportion of micropapillary structures is <10%, the invasive ability of the cancer is significantly higher compared with that of the same pathological type of breast cancer without IMPC components (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Invasive micropapillary carcinoma (IMPC) is a relatively rare but highly aggressive histological subtype that accounts for 0.9% to 8.4% of breast cancer cases, [1][2][3][4][5][6][7][8][9][10] which is often accompanied by extensive lymph node metastasis (LNM), lymphovascular invasion (LVI), high histologic grade, lymph node extracapsular extension, etc. 1,5,[7][8][9][10][11][12][13][14] Although these factors related to the highly local aggressive biological behavior of IMPC have been reported, it remained inconclusive whether this malignant behavior could translate into unfavorable prognosis, 7,15,16 even though that relationship has been widely accepted.…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed that the IDC + IMPC patients had significantly worse DFS and OS compared to those with pure IDC and IDC + DCIS ( P < .001). Lewis et al [ 39 ] carried out a retrospective analysis and reported that patients of IMPC with triple-negative molecular subtypes had worse OS (hazard ratio 7.28, P < .001). Therefore, based on the above reports and our findings, we believe that IMPC is a unique subtype with poor prognosis, and its malignancy is significantly higher than that of patients without an IMPC component.…”
Section: Discussionmentioning
confidence: 99%